IMPLEMENTASI KEBIJAKAN ALOKASI DANA DESA DALAM PENGELOLAAN POTENSI DESA KUTUH KECAMATAN KUTA SELATAN KABUPATEN BADUNG - Resdyanti, Ni Putu Mulya; S.Fil.,MA., Bandiyah; Dwi Wismayanti, S.E.,M.AP., Kadek Wiwin (CITIZEN CHARTER, 2015)
ABSTRAK Â Kutuh village is the youngest village in South Kuta District which is formally formed in 2002 as an effect of expansion of Ungasan village and become one of receiver of minimum allocation village grant (ADD) in Badung Regency. From the problem above therefore the aim of this study is to know the implementation of ADD in managing the village potency in Kutuh village in 2008-2013. The method of this study is descriptive qualitative. The data collected by observation and interview. Some conclusions were got in this study: First, implementation of ADD in Kutuh village runs well. From 2008 to 2010 ADD was the biggest grant that received by Kutuh village that is use to maintain some community empowerment programs, stationery, additional salary for headman and some of village functionary, and also the development of the village potency in tourism field that is development of Pandawa Beach. However in 2011 to 2013 ADD that received by Kutuh village was decrease that makes an effect in village finance. Second, the problem in financial can be solved by Kutuh village with the realization in development of village potency in tourism field because of I Nyoman Mesir as an innovative, communicative, and has high motivation to increase the community prosperity headman in period 2002-2013. He also helped by the village functionary that has good human resources and performance and also supported by adequate facilities and infrastructure. Third, the succeed of village government in Kutuh on implementing ADD proved by no manipulation or misappropriation in ADD. Key words: Implementation Policy, Allocation Village Grant, Management Potency of Kutuh Village